Implementation of group based exercises by peer instructors : a feasibility study in the elderly population - Patil, Radhika (2009)
Background and purpose of the study By the year 2035, the number of persons ≥ 75 years of age will have doubled in Finland. There is convincing evidence for the importance of regular, moderate intensity physical activity for public health gain. Exercise programs need to be developed that can reach the elderly effectively, make optimal use of available resources and are cost effective, thus augmenting state services. The purpose of this study is to evaluate the process and feasibility of a program where peer instructors were educated to implement group based exercises in local pensioner’s societies in Finland.